A review of the blennioid fish family Tripterygiidae (Perciformes) in the Red Sea, with description of Enneapterygius qirmiz, and reinstatement of Enneapterygius altipinnis Clark, 1980 - Holleman, Wouter; Bogorodsky, Sergey V. (Zootaxa, 2012)
The fishes of the blennioid family Tripterygiidae of the Red Sea are reviewed. Twelve species are recognised: Norfolkiabrachylepis, Helcogramma obtusirostris, H. steinitzi and nine species of Enneapterygius. Enneapterygius qirmiz sp. nov.is described for a species originally described, but not named, by Clark (1980), of which the specimens on which she hadbased her description had become lost. Clark’s (1980) Enneapterygius altipinnis is re-instated as a valid species, and itsinclusion as one of a complex of several species is discussed. Enneapterygius ventermaculus reported as first record forthe Red Sea. Detailed colour descriptions are given for all species, including their colour underwater where possible, as many of the species are cryptic and difficult to identify.